Lithium ion battery electrolyte and application thereof
By using specific components of electrolyte in lithium-ion battery electrolyte, the problem of insufficient electrochemical stability of lithium-ion batteries during large-scale charging is solved, and the fast charging and dynamic performance of the battery is improved.
Patent Information
- Application Number
- CN202411958908.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
When charging with large-scale lithium-ion batteries, due to the limitations of lithium-ion migration rate and the lithium-embedding capability of the negative electrode, lithium-ion side is extremely easy to be discharged, and the electrochemical stability is poor, which cannot improve the fast charging performance of the battery.
Provided is a lithium-ion battery electrolyte containing a first solvent (such as trifluorotoluene) and a second solvent (such as methyl ethyl carbonate), and a first additive (compound with a specific structure). These components work together to improve the electrochemical stability of the electrolyte and capture the acidic substances generated by the decomposition of lithium salts in a timely manner to protect the stability of the interface phase.
By improving the electrochemical stability and kinetic performance of the electrolyte, the fast charging performance and cycle life of lithium-ion batteries are significantly improved, and the impedance of the battery is increased and the capacity reduction is reduced.
Smart Images

Figure CN119764568A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of power batteries, and in particular to a lithium-ion battery electrolyte and applications thereof. Background Art
[0002] At present, lithium-ion batteries are developing rapidly in the fields of electric vehicles and large-scale energy storage, occupying a large market share. With the widespread application of lithium-ion batteries, consumers have also had higher demands on the energy density and cycle life of lithium-ion batteries. Although high-nickel positive electrode materials or silicon negative electrode materials with high specific capacity can improve the energy density of lithium-ion batteries, they will increase the impedance of the battery, affect the battery's kinetic performance and cycle life, and cause the decomposition of lithium salts to produce acidic substances, destroy the interface phase, and deteriorate the performance of the battery.
[0003] Moreover, with the rapid development of lithium-ion batteries in electric vehicles and large-scale energy storage, more stringent requirements have been put forward for the fast charging performance of batteries to shorten the charging time of batteries. However, at high rates, the current lithium-ion batteries are very easy to precipitate lithium on the negative electrode side due to the limitations of the migration rate of lithium ions in the electrolyte system and the lithium insertion capacity of the negative electrode. Therefore, the electrochemical stability of the existing electrolyte system is poor and it is impossible to improve the fast charging performance of the battery. Summary of the invention
[0004] The present invention proposes a lithium ion battery electrolyte and its application. The lithium ion battery electrolyte and its application provided by the present invention can, on the one hand, improve the electrochemical stability and kinetic performance of the electrolyte; on the other hand, can timely capture the acidic substances produced by the decomposition of lithium salts to avoid the destruction of the interface phase, thereby jointly improving the fast charging performance and kinetic performance of the battery.
[0005] In order to solve the above technical problems, the present invention provides a lithium ion battery electrolyte, comprising at least the following components:
[0006] A solvent, comprising a first solvent and a second solvent, wherein the first solvent is selected from at least one of trifluorotoluene, difluorobenzene, trifluorobenzene, toluene, ethylbenzene, decafluoropentane, perfluorohexanone, perfluorobutyl ethyl ether or perfluorobutyl methyl ether, and the second solvent is selected from at least one of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate or ethylene carbonate;
[0007] lithium salts; and
[0008] The additive comprises a first additive, wherein the first additive has a general structural formula of:
[0009] Wherein, R1, R2 and R3 are each independently selected from one of substituents having 1-6 carbon atoms, 0-4 unsaturation degrees and 0-3 heteroatoms, and the heteroatoms are selected from at least one of oxygen, nitrogen or sulfur.
[0010] In one embodiment of the present invention, the content of the first solvent in the electrolyte is 25wt%-55wt%.
[0011] In one embodiment of the present invention, the content of the second solvent in the electrolyte is 25wt%-55wt%, and the mass ratio of the second solvent to the first solvent is 1:1.83-1.25:1.
[0012] In one embodiment of the present invention, the substituent is selected from at least one of an alkyl group, an alkenyl group, an alkynyl group, a carbonyl group, an ester group, an amino group or a heterocycle.
[0013] In one embodiment of the present invention, the first additive is selected from Compound 1, Compound 2 or At least one of compound 3.
[0014] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.01 wt %-2 wt %.
[0015] In one embodiment of the present invention, the additive also includes a second additive, the second additive is selected from at least one of lithium difluorophosphate, lithium difluorobisoxalate phosphate or lithium difluorobisoxalate borate, the content of the second additive in the electrolyte is 0.01wt%-1.2wt%, and the mass ratio of the first additive to the second additive is (0.3-0.6):1.
[0016] In one embodiment of the present invention, the additive further includes a third additive, the third additive is selected from at least one of tripropynyl phosphate, tri(trimethylsilyl) phosphate or methylene disulfonate, and the content of the third additive in the electrolyte is 0.01wt%-1wt%.
[0017] In one embodiment of the present invention, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethyl)sulfonylimide, and the content of the lithium salt in the electrolyte is 10 wt %-20 wt %.
[0018] The present invention also provides a lithium ion battery, comprising at least:
[0019] Positive electrode;
[0020] Negative electrode;
[0021] A separator, disposed between the positive electrode sheet and the negative electrode sheet; and
[0022] The electrolyte is selected from the above-mentioned lithium ion battery electrolyte.
[0023] In summary, the present invention proposes a lithium-ion battery electrolyte and its application, wherein the first solvent can regulate the solvation structure of the electrolyte, improve the electrochemical stability of the electrolyte, and thereby improve the fast charging performance of the battery. The first additive and the first solvent act synergistically to timely capture the acidic substances produced by the decomposition of the lithium salt, avoid the damage of the acidic substances to the solid electrolyte interface (Solid Electrolyte Interphase, SEI) membrane and the electrochemical interface (Chemical-Electrochemical Interface, CEI) membrane, and improve the stability of the interfacial phase, thereby further significantly improving the fast charging performance of the battery. The first solvent and the second solvent can make the electrolyte have both good electrochemical stability and good kinetic properties, thereby improving the fast charging performance and kinetic performance of the battery. The second additive and the third additive can further improve the fast charging performance and kinetic performance of the battery. DETAILED DESCRIPTION
[0024] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0025] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.
[0026] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] The present invention provides a lithium ion battery electrolyte, which at least includes a solvent, a lithium salt and an additive, wherein the solvent includes a first solvent and a second solvent, the first solvent is selected from at least one of trifluorotoluene, difluorobenzene, trifluorobenzene, toluene, ethylbenzene, decafluoropentane, perfluorohexanone, perfluorobutyl ethyl ether or perfluorobutyl methyl ether, and the second solvent is selected from at least one of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate or ethylene carbonate, and the additive includes a first additive, and the first additive has a general structural formula of: Wherein, R1, R2 and R3 are each independently selected from a substituent having 1-6 carbon atoms, 0-4 unsaturation and 0-3 heteroatoms, and the heteroatoms are selected from at least one of oxygen, nitrogen or sulfur. In the lithium ion battery electrolyte provided by the present invention, the first solvent and the first additive act synergistically to improve the electrochemical stability and kinetic performance of the electrolyte, and can timely capture the acidic substances generated by the rapid reaction of the salt anions, improve the stability of the interface phase, and thus jointly improve the fast charging performance of the lithium ion battery.
[0028] In one embodiment of the present invention, the first solvent is, for example, a non-polar diluent, which can regulate the solvation structure of the electrolyte, improve the electrochemical stability of the electrolyte, and thus improve the fast charging performance of the battery. Specifically, since the solubility of non-polar diluents in lithium salts is low and they do not have a direct coordination effect with lithium ions, the introduction of non-polar diluents can reduce the free solvent molecules in the electrolyte, promote the coordination of lithium ions and anions, and form a solvation structure dominated by anions, effectively improving the lithium ion migration number. In an electrolyte with such a solvation structure, the salt anions at the electrode / electrolyte interface will preferentially and more decompose into inorganic compounds including lithium fluoride, and the decomposition of the solvent at the interface will be reduced, thereby enhancing the ionic conductivity of the interface phase.
[0029] In one embodiment of the present invention, for the solvent, the content of the first solvent in the electrolyte is, for example, 25wt%-55wt%, and for example, 30wt%-45wt%, and the content of the second solvent in the electrolyte is, for example, 25wt%-55wt%, and the mass ratio of the second solvent to the first solvent is, for example, 1:2.4-1.183:1, and further, for example, 1:1.83-1.25:1. When the mass ratio of the second solvent to the first solvent is less than 1:2.4, the content of the first solvent is too much, and there is not enough second solvent in the electrolyte to dissolve and dissociate the lithium salt, resulting in that the kinetic properties of the electrolyte will be affected, and the battery cannot play a good capacity. When the mass ratio of the second solvent to the first solvent is greater than 1.183:1, the content of the first solvent is too little, and the solvation structure of the electrolyte cannot be effectively regulated, resulting in that the electrochemical stability of the electrolyte cannot be improved, thereby affecting the fast charging performance of the battery. Therefore, by controlling the mass ratio of the second solvent to the first solvent, the electrolyte can have both good electrochemical stability and good kinetic performance, thereby improving the fast charging performance and kinetic performance of the battery.
[0030] In one embodiment of the present invention, in the first additive, the substituents of R1, R2 and R3 are independently selected from alkyl, alkenyl, alkynyl, carbonyl, ester, amino or heterocyclic rings. Specifically, in this embodiment, the first additive is selected from Compound 1, Compound 2 or At least one of compound 3, etc. Although the first solvent can improve the fast charging performance of the battery, when the battery is charged at a high rate, the decomposition rate of the lithium salt is accelerated, and more acidic substances are produced, resulting in an accelerated acid rise rate of the electrolyte system. By introducing the first additive as an acid-suppressing additive, the acidic substances produced by the decomposition of the lithium salt can be captured in time, avoiding the damage of the acidic substances to the SEI membrane and the CEI membrane, and improving the stability of the interfacial phase, thereby further improving the fast charging performance of the battery.
[0031] In one embodiment of the present invention, the content of the first additive in the electrolyte is, for example, 0.01wt%-2wt%, and further, for example, 0.1wt%-0.5wt%. By controlling the content of the first additive, it is possible to remove the acidic substances generated during the battery cycle while avoiding the problems of increased viscosity and decreased conductivity of the electrolyte caused by excessive content of the first additive, thereby improving the dynamic performance of the battery and avoiding increased impedance and decreased capacity of the battery.
[0032] In one embodiment of the present invention, the additive further includes a second additive, and the second additive is, for example, a lithium salt additive, and the lithium salt additive is, for example, selected from at least one of lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiODFP) or lithium difluorooxalate borate (LiDFOB). Among them, the content of the second additive in the electrolyte is, for example, 0.01wt%-1.2wt%, and the mass ratio of the first additive to the second additive is, for example, (0.3-0.6):1. By introducing the second additive and controlling the mass ratio of the first additive to the second additive, the fast charging performance and dynamic performance of the battery can be further improved.
[0033] In one embodiment of the present invention, the additive further includes a third additive, the third additive is selected from at least one of tripropynyl phosphate, tri(trimethylsilyl) phosphate or methylene disulfonate, and the content of the third additive in the electrolyte is, for example, 0.01wt%-1wt%. By introducing the third additive and controlling the content of the third additive, the fast charging performance and dynamic performance of the battery can be further improved.
[0034] In one embodiment of the present invention, the lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethyl)sulfonyl imide (LiFSI), lithium bis(trifluoromethyl)sulfonyl imide (LiTFSI), lithium dioxalate borate (LiBOB), LiODFP, lithium difluorooxalate borate (LiODFB), LiPO2F2 or lithium trifluoromethylsulfonate (CF3SO3Li). Further, in this embodiment, the lithium salt is selected from at least one of LiPF6, LiFSI or LiTFSI, and the content of the lithium salt in the electrolyte is, for example, 10wt%-20wt%, and the concentration of the lithium salt in the electrolyte is, for example, 0.1mol / L-2mol / L, and for example, 0.5mol / L-1.5mol / L.
[0035] In one embodiment of the present invention, when preparing the electrolyte, in a glove box with a stable gas atmosphere such as argon, a battery-grade first solvent and a second solvent are mixed evenly according to a mass ratio to obtain a mixed solvent, and a lithium salt and an additive are added to the mixed solvent and mixed evenly to prepare a lithium-ion battery electrolyte. The argon content in the glove box is, for example, greater than or equal to 99.999%, the oxygen content is, for example, less than 0.1 ppm, and the water content is, for example, less than 0.1 ppm.
[0036] The present invention also proposes a lithium-ion battery, and the lithium-ion battery includes a positive electrode plate, a separator, a negative electrode plate and an electrolyte. The separator is located between the positive electrode plate and the negative electrode plate to prevent a short circuit between the positive electrode plate and the negative electrode plate, so that lithium ions can pass through. The electrolyte is filled between the positive electrode plate, the separator and the negative electrode plate, and the electrolyte is the above-mentioned lithium-ion battery electrolyte, which plays a role in conducting ions. Among them, the lithium-ion battery is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery or a cylindrical battery, etc. The present invention does not specifically limit the type and type of the lithium-ion battery.
[0037] In one embodiment of the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer coated on at least one surface of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric.
[0038] In one embodiment of the present invention, the positive electrode active layer includes a positive electrode active material, a conductive agent and a binder. Among them, the ratio of the positive electrode active material, the conductive agent and the binder can be selected according to actual needs. In this embodiment, the positive electrode active material is, for example, a high-nickel positive electrode material, and the high-nickel positive electrode material is selected from at least one of lithium nickel manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide. By selecting a high-nickel positive electrode material as the positive electrode active material, the energy density of the battery can be improved due to the high specific capacity of the high-nickel positive electrode material.
[0039] In one embodiment of the present invention, the conductive agent is selected from at least one of conductive carbon black, acetylene black, carbon nanotubes or graphene, and the binder is selected from at least one of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene butadiene rubber (SBR).
[0040] In one embodiment of the present invention, the positive electrode current collector is, for example, aluminum foil, and the positive electrode active material is, for example, LiNi 0.9 Mn 0.05 Co 0.05 O2, the conductive agent is, for example, acetylene black, and the binder is, for example, PVDF. The positive electrode active material, acetylene black and PVDF are mixed in a mass ratio of, for example, 95:3:2, dissolved in an organic solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry, and then the positive electrode slurry is evenly coated on an aluminum foil, and then transferred to an oven for drying after drying at room temperature, and a positive electrode sheet is obtained through cold pressing and slitting. Among them, the organic solvent is, for example, N-methylpyrrolidone (NMP).
[0041] In one embodiment of the present invention, the negative electrode plate includes, for example, a negative electrode current collector and a negative electrode active layer coated on at least one surface of the negative electrode current collector, wherein the negative electrode current collector is, for example, selected from a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector, or a stainless steel current collector.
[0042] In one embodiment of the present invention, the negative electrode active layer includes a negative electrode active material, a conductive agent, a thickener, and a binder. The proportions of the negative electrode active material, the conductive agent, the thickener, and the binder can be selected according to actual needs. In this embodiment, the negative electrode active material is selected from at least one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide, silicon carbon compound, or lithium titanate.
[0043] In one embodiment of the present invention, the conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes or graphene, etc. The thickener includes, for example, carboxymethyl cellulose sodium (CMC-Na), etc. The binder is selected from at least one of PVDF, PEO, PA, polypropylene, polyacrylate, polyvinyl ether, PMMA, polyhexafluoropropylene or SBR, etc.
[0044] In one embodiment of the present invention, the negative electrode current collector is, for example, copper foil, the negative electrode active material includes, for example, artificial graphite and silicon oxide, the content of artificial graphite in the negative electrode active material is 90wt%, the content of silicon oxide in the negative electrode active material is 10wt%, the conductive agent is, for example, acetylene black, the thickener is, for example, CMC-Na, and the binder is, for example, SBR. Specifically, the negative electrode active material, the conductive agent, the thickener and the binder are mixed in a mass ratio of 96:2:1:1, and deionized water solvent is added, and then the mixture is stirred and mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry, and the negative electrode slurry is coated on the copper foil, and then transferred to an oven for drying after drying at room temperature, and the negative electrode sheet is obtained through cold pressing and slitting.
[0045] In one embodiment of the present invention, the diaphragm includes, for example, a base film and a coating, wherein the base film is, for example, a single-layer polypropylene (PP) film, a single-layer polyethylene (PE) film, a double-layer PP / PE film, a double-layer PP / PP film, or a three-layer PP / PE / PP film, etc., the thickness of the base film is, for example, 9 μm-15 μm, and the coating is disposed on the base film, the material of the coating includes nano-alumina, etc., and the thickness of the coating is, for example, 1 μm-5 μm. In this embodiment, for example, a single-layer PE film with a thickness of 9 μm is selected as the base film, and a nano-alumina coating with a thickness of 3 μm is disposed on the base film.
[0046] In one embodiment of the present invention, the positive electrode sheet, the separator and the negative electrode sheet are placed in sequence, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role. Then, the aluminum plastic film is wrapped, transferred to 80°C for baking to remove water, and the prepared lithium ion battery electrolyte is injected at 3.0g / Ah and then sealed. After standing, hot and cold pressing, formation, clamping and capacity division, a soft-pack lithium ion secondary battery with a capacity of 1Ah is obtained.
[0047] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.
[0048] Example 1
[0049] Preparation of positive electrode: LiNi 0.9 Mn 0.05 Co 0.05 O2, acetylene black and PVDF are mixed in a mass ratio of 95:3:2, dissolved in an organic solvent NMP, and stirred under a vacuum mixer until the system is uniform to obtain a positive electrode slurry. The positive electrode slurry is then evenly coated on an aluminum foil, and then dried at room temperature and transferred to an oven for drying. The positive electrode sheet is obtained through processes such as cold pressing and slitting.
[0050] Preparation of negative electrode sheet: artificial graphite and silicon oxide are mixed in a mass ratio of 9:1 to obtain negative electrode active material. Negative electrode active material, acetylene black, CMC-Na and SBR are mixed in a mass ratio of 96:2:1:1, and deionized water solvent is added, and then fully stirred and mixed under the action of a vacuum mixer to obtain negative electrode slurry, which is coated on copper foil, and then transferred to an oven for drying after drying at room temperature, and then cold pressed and cut to obtain negative electrode sheet.
[0051] Preparation of electrolyte: In a glove box with an argon content of 99.999%, an oxygen content of less than 0.1ppm and a moisture content of less than 0.1ppm, according to the composition of the electrolyte described in Table 1, the first solvent trifluorotoluene and the second solvent methyl ethyl carbonate of battery grade are mixed in a mass ratio of 1:1 to obtain a mixed solvent, and then LiPF6 and compound 1 are added to the mixed solvent and mixed evenly to prepare a lithium ion battery electrolyte. The contents of LiPF6 and compound 1 in the electrolyte are 15wt% and 0.3wt%, respectively.
[0052] Selection of diaphragm: A single-layer PE film with a thickness of 9 μm is used as a base film, and a nano-aluminum oxide coating with a thickness of 3 μm is coated on the base film to obtain a diaphragm.
[0053] Preparation of the battery: The positive electrode, separator and negative electrode are placed in sequence, and wrapped with aluminum-plastic film, transferred to 80°C for baking to remove water, and then 3.0g / Ah of the lithium-ion battery electrolyte prepared above is injected and sealed. After standing, hot and cold pressing, formation, clamping and capacity division, a soft-pack lithium-ion battery with a capacity of 1Ah is obtained.
[0054] Example 2
[0055] The mass ratio of the second solvent ethyl methyl carbonate to the first solvent trifluorotoluene in the mixed solvent is 1:3.25, and the other steps are the same as those in Example 1.
[0056] Example 3
[0057] The mass ratio of the second solvent ethyl methyl carbonate to the first solvent trifluorotoluene in the mixed solvent is 1:2.4, and the other steps are the same as those in Example 1.
[0058] Example 4
[0059] The mass ratio of the second solvent ethyl methyl carbonate to the first solvent trifluorotoluene in the mixed solvent is 1:1.83, and the other steps are the same as those in Example 1.
[0060] Example 5
[0061] The mass ratio of the second solvent ethyl methyl carbonate to the first solvent trifluorotoluene in the mixed solvent is 1:1.25, and the other steps are the same as those in Example 1.
[0062] Example 6
[0063] The mass ratio of the second solvent ethyl methyl carbonate to the first solvent trifluorotoluene in the mixed solvent is 1.25:1, and the other steps are the same as those in Example 1.
[0064] Example 7
[0065] The mass ratio of the second solvent ethyl methyl carbonate to the first solvent trifluorotoluene in the mixed solvent is 1.183:1, and the other steps are the same as those in Example 1.
[0066] Example 8
[0067] The mass ratio of the second solvent ethyl methyl carbonate to the first solvent trifluorotoluene in the mixed solvent is 2.4:1, and the other steps are the same as those in Example 1.
[0068] Example 9
[0069] The second solvent is diethyl carbonate, and the other steps are the same as in Example 1.
[0070] Example 10
[0071] The first solvent is toluene, and the other steps are the same as in Example 1.
[0072] Embodiment 11
[0073] The first solvent is ethylbenzene, and the other steps are the same as in Example 1.
[0074] Example 12
[0075] The first solvent is decafluoropentane, and the other steps are the same as those in Example 1.
[0076] Example 13
[0077] The first solvent is perfluorobutyl ether, and the other steps are the same as those in Example 1.
[0078] Embodiment 14
[0079] The first solvent is perfluorobutyl methyl ether, and the other steps are the same as those in Example 1.
[0080] Embodiment 15
[0081] The content of compound 1 in the electrolyte is 0.1 wt %. The other steps are the same as those in Example 1.
[0082] Example 16
[0083] The content of compound 1 in the electrolyte is 2 wt %, and the other steps are the same as those in Example 1.
[0084] Embodiment 17
[0085] The electrolyte contains compound 2, and the contents of compound 2 and compound 1 in the electrolyte are 0.3wt% and 0, respectively. Other steps are the same as those in Example 1.
[0086] Embodiment 18
[0087] The electrolyte contains compound 3, and the contents of compound 3 and compound 1 in the electrolyte are 0.3wt% and 0, respectively. Other steps are the same as those in Example 1.
[0088] Embodiment 19
[0089] The electrolyte contains a second additive LiPO2F2, and the content of LiPO2F2 in the electrolyte is 1.2wt%. The other steps are the same as those in Example 1.
[0090] Embodiment 20
[0091] The electrolyte contains a second additive LiPO2F2, and the content of LiPO2F2 in the electrolyte is 1 wt %. The other steps are the same as those in Example 1.
[0092] Embodiment 21
[0093] The electrolyte contains a second additive LiPO2F2, and the content of LiPO2F2 in the electrolyte is 0.5wt%. The other steps are the same as those in Example 1.
[0094] Embodiment 22
[0095] The electrolyte contains a third additive, tripropynyl phosphate, and the content of tripropynyl phosphate in the electrolyte is 0.01 wt %. The other steps are the same as those in Example 1.
[0096] Embodiment 23
[0097] The electrolyte contains a third additive, tripropynyl phosphate, and the content of tripropynyl phosphate in the electrolyte is 0.5 wt %. The other steps are the same as those in Example 1.
[0098] Embodiment 24
[0099] The electrolyte contains a third additive, tripropynyl phosphate, and the content of tripropynyl phosphate in the electrolyte is 1 wt %. The other steps are the same as those in Example 1.
[0100] Embodiment 25
[0101] The electrolyte contains both the second additive LiPO2F2 and the third additive tripropynyl phosphate, and the contents of LiPO2F2 and tripropynyl phosphate in the electrolyte are 1wt% and 0.5wt% respectively. The other steps are the same as those in Example 1.
[0102] Comparative Example 1
[0103] The electrolyte does not contain the first solvent, and the other steps are the same as those in Example 1.
[0104] Comparative Example 2
[0105] The electrolyte does not contain compound 1, and the other steps are the same as those in Example 1.
[0106] Comparative Example 3
[0107] The electrolyte does not contain compound 1, and the other steps are the same as those in Comparative Example 1.
[0108] Comparative Example 4
[0109] The electrolyte does not contain compound 1, and the other steps are the same as Example 20.
[0110] Comparative Example 5
[0111] The electrolyte does not contain compound 1, and the other steps are the same as Example 23.
[0112] The raw material component contents and raw material mass ratios required for the electrolytes prepared in the embodiments and comparative examples are shown in Table 1.
[0113] Table 1. Composition of the electrolyte in Examples 1-25 and Comparative Examples 1-5
[0114]
[0115]
[0116] In the present invention, performance tests were performed on lithium-ion batteries prepared using different electrolyte ratios in Examples 1-25 and Comparative Examples 1-5. The test results are shown in Table 2.
[0117] In one embodiment of the present invention, for example, a direct current resistance (DCR) test is performed on a lithium-ion battery. Specifically, at 25°C, after the battery has been allowed to stand for 10 minutes, the battery is charged to 4.3V at a constant current rate of 0.33C, and then the constant voltage is set to 0.05C. After standing for 10 minutes, the battery is discharged to 2.5V at a rate of 0.33C to obtain the theoretical capacity of the battery, and then the battery is charged to 4.3V at a constant current rate of 0.33C, and then the constant voltage is set to 0.05C. After standing for 10 minutes, the battery is discharged to 50% state of charge (SOC) at a rate of 0.33C. After standing for 1 hour, the initial voltage V1 of the battery is recorded, and then the battery is discharged at a current I0 of 4C for 30s, and the battery voltage V2 after discharge is recorded. The DCR of the battery at 50% SOC is calculated according to the following formula:
[0118] DCR=(V1-V2) / I0.
[0119] In one embodiment of the present invention, for example, a fast charge capacity retention rate test is performed on a lithium-ion battery. Specifically, at 25°C, the lithium-ion battery is charged at different rates (0.33C, 1C, 2C, 3C and 4C) to 4.3V, and then charged at a constant voltage of 4.3V until the current is less than 0.05C. After standing for 10 minutes, it is discharged at a constant current of 0.33C to 2.5V. Among them, after each charging rate is cycled twice, it is adjusted to the next rate in turn for charge and discharge cycles, and the charging capacity of the second cycle at a rate of 0.33C and the second cycle at a rate of 4C are recorded as the charging capacity of the lithium-ion battery at 0.33C and 4C, and the fast charge capacity retention rate of a large rate of 4C is calculated according to the following formula:
[0120] Fast charge capacity retention rate (%) = (4C charge capacity / 0.33C charge capacity) × 100%.
[0121] Table 2 Performance test results of lithium ion batteries in Examples 1-25 and Comparative Examples 1-5
[0122] Group DCR(mOhm) Fast charge capacity retention rate (%) Example 1 120.3 83.9 Example 2 128.1 78.3 Example 3 125.4 80.6 Example 4 123.6 84.2 Example 5 120.5 82.6 Example 6 118.3 82.8 Example 7 114.6 80.4 Example 8 111.9 77.9 Example 9 128.7 82.9 Example 10 110.2 82.7 Embodiment 11 118.4 82.9 Example 12 125.6 82.1 Embodiment 13 128.5 84.4 Embodiment 14 128.1 83.5 Embodiment 15 114.6 82.1 Example 16 118.7 82.8 Embodiment 17 118.4 81.2 Embodiment 18 125.8 82.0 Embodiment 19 123.0 83.5 Embodiment 20 118.0 84.3 Embodiment 21 118.4 84.1 Embodiment 22 120.6 84.0 Embodiment 23 121.2 84.4 Embodiment 24 125.3 83.8 Embodiment 25 120.4 84.6 Comparative Example 1 110.7 71.2 Comparative Example 2 117.3 75.3 Comparative Example 3 108.6 68.0 Comparative Example 4 117.9 78.5 Comparative Example 5 120.1 78.7
[0123] Please refer to Table 1 and Table 2. By comparing Comparative Example 1 and Comparative Example 3, it can be seen that when the electrolyte contains the first additive compound 1, the fast charging capacity retention rate of the battery increases, but the increase is very small, which shows that when the first additive is used alone, the electrolyte cannot provide sufficient intrinsic electrochemical stability and cannot significantly improve the fast charging performance of the battery.
[0124] Please refer to Table 1 and Table 2. By comparing Comparative Example 2 and Comparative Example 3, it can be seen that when the electrolyte contains the first solvent trifluorotoluene, although the fast charging capacity retention rate of the battery is significantly increased, the impedance is also significantly increased, which shows that: using the first solvent alone, although it can improve the electrochemical stability of the electrolyte, thereby improving the fast charging performance of the battery, it will accelerate the acid rise rate of the electrolyte system, resulting in the destruction of the interfacial phase and affecting the impedance performance.
[0125] Please refer to Table 1 and Table 2. By comparing Example 1 and Comparative Examples 1-3, it can be seen that when the electrolyte contains both the first solvent trifluorotoluene and the first additive compound 1, the fast charging capacity retention rate of the battery is significantly increased, and the impedance does not increase significantly. This indicates that: the first solvent and the first additive act synergistically, the first solvent can improve the electrochemical stability of the electrolyte and enhance the fast charging performance of the battery. At the same time, the first additive can inhibit the acid rise rate of the electrolyte, avoid the destruction of the interfacial phase, enhance the kinetic properties of the electrolyte, improve the impedance of the battery, and further enhance the fast charging performance of the battery.
[0126] Please refer to Table 1 and Table 2. Comparative Examples 1-8 show that when the mass ratio of the second solvent to the first solvent increases from 1:3.25 to 2.4:1, the impedance of the battery gradually decreases as a whole. However, when the mass ratio of the second solvent to the first solvent is greater than 1.183:1, the fast charge capacity retention rate of the battery is significantly reduced to less than 80%. When the mass ratio of the second solvent to the first solvent is less than 1:2.4, the impedance of the battery is maintained at a higher value of about 128mOhm, indicating that when the mass ratio of the second solvent to the first solvent is too small, the content of the first solvent is too much, and there is not enough second solvent in the electrolyte to dissolve and dissociate the lithium salt, resulting in the kinetic performance of the electrolyte being affected, and the battery cannot play a good capacity. When the mass ratio of the second solvent to the first solvent is too large, the content of the first solvent is too little, and the solvation structure of the electrolyte cannot be effectively regulated, resulting in the electrochemical stability of the electrolyte cannot be improved, thereby affecting the fast charge performance of the battery. Therefore, by controlling the mass ratio of the second solvent to the first solvent, the fast charge performance and kinetic performance of the battery can be taken into account.
[0127] Please refer to Table 1 and Table 2. By comparing Example 1 and Example 9, it can be seen that when ethyl methyl carbonate is used as the second solvent, the fast charging capacity retention rate of the battery is greater and the impedance of the battery is smaller, which indicates that the fast charging performance and dynamic performance of the battery can be improved by controlling the type of the second solvent.
[0128] Please refer to Table 1 and Table 2. By comparing Example 1 with Examples 10-14, it can be seen that when trifluorotoluene, toluene, ethylbenzene, decafluoropentane, perfluorobutyl ethyl ether and perfluorobutyl methyl ether are used as the first solvent, the fast charge capacity retention rate of the battery is relatively large, and the impedance of the battery is not greatly affected, which shows that trifluorotoluene as the first solvent can comprehensively improve the fast charge performance and dynamic performance of the battery. Therefore, by controlling the type of the first solvent, the fast charge performance and dynamic performance of the battery can be further improved.
[0129] Please refer to Table 1 and Table 2. By comparing Example 1 and Examples 15-16, it can be seen that as the content of the first additive compound 1 in the electrolyte increases from 0.1wt% to 0.3wt% and 2wt%, the impedance and fast charge capacity retention rate of the battery increase, indicating that: the increase in the content of the first additive can remove more acidic substances generated during the battery cycle, inhibit the acid rise rate of the electrolyte, protect the stability of the interface phase, and improve the fast charge performance of the battery. However, when the content of the first additive is too large, the viscosity of the electrolyte increases and the conductivity decreases, resulting in an increase in impedance and affecting the dynamic performance of the battery. Therefore, by controlling the content of the first additive, the fast charge performance and dynamic performance of the battery can be taken into account.
[0130] Please refer to Table 1 and Table 2. By comparing Example 1 with Examples 17-18, it can be seen that when Compound 1, Compound 2 and Compound 3 are used as the first additive, the fast charge capacity retention rate of the battery is greater, that is, the fast charge performance of the battery is better. When Compound 2 is used as the first additive, the impedance of the battery is smaller, that is, the dynamic performance of the battery is better. Therefore, by controlling the type of the first additive, the dynamic performance and fast charge performance of the battery can be further improved.
[0131] Please refer to Table 1 and Table 2. By comparing Example 1, Example 20, Comparative Example 2 and Comparative Example 4, it can be seen that for the first additive and the second additive, when the electrolyte contains the second additive LiPO2F2 alone, the fast charge capacity retention rate of the battery increases, but the increase is very small, indicating that the second additive alone cannot significantly improve the fast charge performance of the battery. When the electrolyte contains the first additive compound 1 alone, the fast charge capacity retention rate of the battery increases, but the impedance also increases, indicating that the first additive can improve the fast charge performance of the battery, but affects the dynamic performance of the battery. When the electrolyte contains both the first additive compound 1 and the second additive LiPO2F2, the fast charge capacity retention rate of the battery is greater and the impedance is reduced, indicating that by adding the second additive to the electrolyte containing the first additive, the dynamic performance and fast charge performance of the battery can be further significantly improved.
[0132] Please refer to Table 1 and Table 2. Comparing Examples 19-21, it can be seen that as the mass ratio of the first additive and the second additive increases from 0.3:1.2 to 0.3:1, the impedance of the battery decreases, and the fast charge capacity retention rate increases, that is, the battery's dynamic performance and fast charge performance are improved. However, when the mass ratio continues to increase from 0.3:1 to 0.3:0.5, the impedance of the battery increases, and the fast charge capacity retention rate decreases, that is, the battery's dynamic performance and fast charge performance are affected, indicating that: the second additive is large in amount and difficult to dissolve, resulting in an increase in electrolyte viscosity and a decrease in conductivity, thereby affecting the battery's dynamic performance and fast charge performance. Therefore, by controlling the mass ratio of the first additive and the second additive, the battery's dynamic performance and fast charge performance can be improved.
[0133] Please refer to Table 1 and Table 2. By comparing Example 1, Example 23, Comparative Example 2 and Comparative Example 5, it can be seen that for the first additive and the third additive, when the electrolyte contains the third additive tripropynyl phosphate alone, the increase in the fast charge capacity retention rate of the battery is relatively insignificant, indicating that: the third additive alone is difficult to effectively improve the fast charge performance of the battery. When the electrolyte contains the first additive compound 1 alone, the fast charge capacity retention rate of the battery increases, indicating that: the first additive can improve the fast charge performance of the battery. When the electrolyte contains both the first additive compound 1 and the third additive tripropynyl phosphate, the fast charge capacity retention rate of the battery is greater, indicating that: by adding the third additive to the electrolyte containing the first additive, the fast charge performance of the battery can be further improved.
[0134] Please refer to Table 1 and Table 2. Comparative Examples 22-24 show that as the content of the third additive tripropynyl phosphate in the electrolyte increases from 0.01wt% to 1wt%, the impedance of the battery increases, and the fast charge capacity first increases and then decreases, indicating that: as the content of the third additive increases, although the dynamic performance of the battery is affected, the fast charge performance shows a trend of first increasing and then decreasing. Therefore, by controlling the content of the third additive, the fast charge performance of the battery can be improved while the dynamic performance of the battery is not significantly affected.
[0135] Please refer to Table 1 and Table 2. By comparing Example 1, Example 20, Example 23 and Example 25, it can be seen that when the electrolyte contains the first additive, the second additive and the third additive at the same time, the fast charging capacity retention rate of the battery is the largest and the impedance value is not high, which indicates that the first additive, the second additive and the third additive work synergistically to significantly improve the fast charging performance while the battery's kinetic performance is not significantly affected.
[0136] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.
[0137] In summary, the present invention proposes a lithium-ion battery electrolyte and its application. By introducing a first solvent into the electrolyte, the electrochemical stability of the electrolyte can be improved, thereby improving the fast charging performance of the battery. By introducing a first additive into the electrolyte, the first additive can timely capture the acidic substances produced by the decomposition of the lithium salt, avoid the damage of the acidic substances to the SEI film and the CEI film, improve the stability of the interfacial phase, thereby further improving the fast charging performance of the battery, and can also reduce the viscosity of the electrolyte, improve the conductivity of the electrolyte, avoid the increase of the impedance of the battery, and improve the dynamic performance of the battery.
[0138] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.
[0139] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.
Claims
1. A lithium ion battery electrolyte, characterized in that: At least the following components are included: A solvent, comprising a first solvent and a second solvent, wherein the first solvent is selected from at least one of trifluorotoluene, difluorobenzene, trifluorobenzene, toluene, ethylbenzene, decafluoropentane, perfluorohexanone, perfluorobutyl ethyl ether or perfluorobutyl methyl ether, and the second solvent is selected from at least one of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate or ethylene carbonate; lithium salts; and The additive comprises a first additive, wherein the first additive has a general structural formula of: Wherein, R1, R2 and R3 are each independently selected from one of substituents having 1-6 carbon atoms, 0-4 unsaturation degrees and 0-3 heteroatoms, and the heteroatoms are selected from at least one of oxygen, nitrogen or sulfur.
2. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the first solvent in the electrolyte is 25wt%-55wt%.
3. The lithium ion battery electrolyte according to claim 1, characterized in that The content of the second solvent in the electrolyte is 25wt%-55wt%, and the mass ratio of the second solvent to the first solvent is 1:1.83-1.25:
1.
4. The lithium ion battery electrolyte according to claim 1, characterized in that: The substituent is selected from at least one of an alkyl group, an alkenyl group, an alkynyl group, a carbonyl group, an ester group, an amino group or a heterocycle.
5. The lithium ion battery electrolyte according to claim 1, characterized in that: The first additive is selected from At least one of .
6. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the first additive in the electrolyte is 0.01wt%-2wt%.
7. The lithium ion battery electrolyte according to claim 1, characterized in that: The additives also include a second additive, which is selected from at least one of lithium difluorophosphate, lithium difluorobisoxalate phosphate or lithium difluorobisoxalate borate, the content of the second additive in the electrolyte is 0.01wt%-1.2wt%, and the mass ratio of the first additive to the second additive is (0.3-0.6):
1.
8. The lithium ion battery electrolyte according to claim 1, characterized in that: The additives further include a third additive, the third additive is selected from at least one of tripropynyl phosphate, tri(trimethylsilyl) phosphate or methylene disulfonate, and the content of the third additive in the electrolyte is 0.01wt%-1wt%.
9. The lithium ion battery electrolyte according to claim 1, characterized in that: The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethyl)sulfonyl imide, and the content of the lithium salt in the electrolyte is 10 wt % to 20 wt %.
10. A lithium ion battery, characterized in that: include: Positive electrode; Negative electrode; A diaphragm, disposed between the positive electrode sheet and the negative electrode sheet; as well as An electrolyte, wherein the electrolyte is selected from the lithium ion battery electrolyte according to any one of claims 1 to 9.
Citation Information
Patent Citations
Electrolyte based on eutectic solvent and lithium ion battery
CN116683031A
Electrolyte and lithium ion secondary battery
CN118572196A
Lithium ion battery electrolyte and application thereof
CN118659031A
Electrolyte composition, photoelectric conversion device and photo-electrochemical cell
EP1089305A2
Nonaqueous electrolytic solution secondary battery
JP2003086246A